Pengaruh Layanan Informasi tentang Pendidikan Seks terhadap Perkembangan Psikoseksual Siswa Kelas X TKK dan TKJ SMKN 4 Pekanbaru T.P 2014/2015 - Monica Silvani Silvani; Zulfan Saam Saam; Abu Asyari Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Related to modern development era, it is the time when sexual education on children and adolescent needs to be improved. It indicates that teachers and counselors have to take part in sexual education. As one of the education components, Guidance and Counseling has an important role in identifying students’ understanding on psychosexual development. The objective of this research was: 1)to describe students’ psychosexual developmentbefore Sex Education Information Service was applied. 2) to describe the process of Sex Education Information Service implementation on students’ psychosexual development. 3) to describe students’ psychosexual development after Sex Education Information Service was applied. 4) to identify students’ psychosexual development differentiation before and after Sex Education Information Service was applied. 5) to identify the effect of Sex Education Information Serviceon students’ psychosexual development. Data collection tool was instrument. The subject of this research was 101first year students of TKK and TKJ SMKN 4 Pekanbaru. Sampling was saturated sample and total sample was 101 samples. The description of students’ psychosexual development before Sex Education Information Service was applied was 29,71% (not good) and 70,29% (fairly good). The improvement of students’ psychosexual development after Sex Education Information Service was applied was 72,28% (fairly good) and 27,72% (good). The correlation coefficient calculation between x1 and x2 was 0,37 and determination coefficient r2 = 0,14. It can be concluded that the effect of Sex Education Information Service on the improvement of students’ psychosexual developmentwas 14%. It means that thitung was bigger than ttabel (27,2<1,960) so that Ha was accepted. In conclusion, there was a significant effect of of sex education information service on psychosexual development of the first year students of TKK and TKJ SMKN 4 Pekanbaru Academic Year 2014 / 2015. Key words : Information Service, Sex Education, Psychosexual Development